2021
DOI: 10.1016/j.cmi.2021.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary long-term consequences of COVID-19 infections after hospital discharge

Abstract: Objectives COVID-19 survivors are reporting residual abnormalities after discharge from the hospital. Limited information is available about this stage of recovery or the lingering effects of the virus on pulmonary function and inflammation. The aim of this study was to describe lung function and to identify biomarkers in serum and induced sputum samples from patients recovering from COVID-19 hospitalisation. Methods Patients admitted to Spanish hospitals with laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 33 publications
3
98
2
3
Order By: Relevance
“…In the present study, 94% of the patients had CT abnormalities at approximately 100 days after symptom onset. This percentage is higher than previous COVID-19 reports because we exclusively examined critical cases ( 21 ) ( 22 ). In one study in which patients requiring invasive mechanical ventilation were excluded, follow-up CT assessments were performed for 100 patients recovering from COVID-19 hospitalization, and the authors found that 52% of the patients had abnormal CT findings at approximately 100 days after the onset of symptoms ( 21 ).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In the present study, 94% of the patients had CT abnormalities at approximately 100 days after symptom onset. This percentage is higher than previous COVID-19 reports because we exclusively examined critical cases ( 21 ) ( 22 ). In one study in which patients requiring invasive mechanical ventilation were excluded, follow-up CT assessments were performed for 100 patients recovering from COVID-19 hospitalization, and the authors found that 52% of the patients had abnormal CT findings at approximately 100 days after the onset of symptoms ( 21 ).…”
Section: Discussioncontrasting
confidence: 58%
“…This percentage is higher than previous COVID-19 reports because we exclusively examined critical cases ( 21 ) ( 22 ). In one study in which patients requiring invasive mechanical ventilation were excluded, follow-up CT assessments were performed for 100 patients recovering from COVID-19 hospitalization, and the authors found that 52% of the patients had abnormal CT findings at approximately 100 days after the onset of symptoms ( 21 ). In another study, 90-day follow-up CT scans were performed for 52 patients recovering from COVID-19 (11 of the patients were in the ICU), and the authors found CT abnormalities in 58% of the patients ( 22 ).…”
Section: Discussioncontrasting
confidence: 58%
“…As of early August, 2021, more than 200 million COVID-19 cases have been confirmed globally, and more than 4•3 million people have died following SARS-CoV-2 infection. 1 The sequelae after recovery from acute COVID-19 have been widely reported [2][3][4][5][6][7][8][9][10][11][12] and have become an increasing concern. In our previous cohort study with a median follow-up time of 6 months after symptom onset, approximately three-quarters of COVID-19 survivors discharged from hospital still had persisting symptoms, and patients who were critically ill during hospital stay had higher risk of lung diffusion impairment and radiographic abnormality than did those who had lower disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two studies included people requiring ICU admission during the acute phase. [25,2729,31,32,3449]…”
Section: Resultsmentioning
confidence: 99%
“…The longest follow-up period in any study was a mean of 221.7 (SD: 10.9) days post-onset. Only 56% (22/39) of studies specified Covid-19 severity [25,2729,31,32,3449], 31% (12/39) treatment received during the acute phase [30,34,35,39,40,44,47,5054], and 62% (24/39) described ventilation support requirements. [3036,39,40,4245,47,48,50,51,5460] Pre-existing comorbidities were reported in the majority of studies (85%, 33/39), with hypertension and diabetes most commonly documented.…”
Section: Resultsmentioning
confidence: 99%